Oil, Exchange Rate, and Dollar Index as Safe Haven in The Period Before and During Covid-19 Pandemic: Examination in Indonesian Capital Market - Adiputri, Bio Labora; Robiyanto, Robiyanto (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2021)
Safe haven is an asset sought by investors, especially when market turmoil occurs. This study aimed to test the role of oil, exchange rate, and Dollar Index as safe havens for the Indonesian capital market in the period before and during the COVID-19 pandemic. Using QREQ and GARCH analysis technique, this study found that oil and exchange rates can be safe haven in the period before and during the COVID-19 pandemic. While the Dollar Index is only able to be a safe haven during COVID-19 pandemic. The results in this study can be considered by investors to choose safe haven instruments.